2001
DOI: 10.1046/j.1365-201x.2001.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia improves atrial tolerance to subsequent anoxia and reduces stress protein expression

Abstract: We tested the hypothesis that 21 days of intermittent hypoxia (IH) increases the tolerance of the spontaneously beating guinea-pig double atria preparation to acute in-vitro hypoxia, and reduces cardiac stress protein expression. A total of 28 guinea-pigs were divided into four groups: (i) IH; (ii) IH + in-vitro hypoxia (IH + IV); (iii) control (CON); (iv) control + in-vitro hypoxia (CON + IV). The IH animals were exposed to 8% O2/0.3% CO2 for 12 h day-1 for 21 days. Normoxic controls were exposed to room air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Under hypoxia stress, cells transactivate a variety of genes in order to adapt to altered metabolic status or, alternatively, to induce irreversible cell toxicity. It was previously reported that HSP70 serves as a key modulator of cellular responses to hypoxia (Mohan et al 2001;Rafiee et al 2003;Guanghe and Feng 2007), and hypoxia-induced HSP70 expression suggests a positive correlation between stress protein expression and protection against myocardial damage (Dillmann and Mestril 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Under hypoxia stress, cells transactivate a variety of genes in order to adapt to altered metabolic status or, alternatively, to induce irreversible cell toxicity. It was previously reported that HSP70 serves as a key modulator of cellular responses to hypoxia (Mohan et al 2001;Rafiee et al 2003;Guanghe and Feng 2007), and hypoxia-induced HSP70 expression suggests a positive correlation between stress protein expression and protection against myocardial damage (Dillmann and Mestril 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Some studies in rodents also reported less dramatic changes in baseline cardiovascular and cognitive parameters (Greenberg et al, 1999; Kraiczi et al, 1999; Reeves et al, 2003; Naghshin et al, 2009; Knight et al, 2011), but it is not clear whether the lesser magnitude of the effects was related to less severe hypoxia (nadirs of 6–10%) or other factors. It is also of note that numerous studies report a positive effect of CIH on endurance, resistance to ischemic injury, glucose disposal, and hypertension (Mohan et al, 2001; Cai et al, 2003; Chiu et al, 2004; Serebrovskaya et al, 2008; Lyamina et al, 2011; Tonini et al, 2011), but the CIH protocols used to achieve these beneficial effects often involve less frequent cycling and less severe hypoxia than those used in studies that aim to model the periodic O 2 desaturations that occur in OSA patients.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, hypoxia reduces the expression of HSP70 in human endothelial cells and atrial tissue [25,27]. In the only study performed with macrophages, low levels of HSP70 were observed in cells exposed to a single period of hypoxia when compared with cells subjected to repeated cycles of hypoxia/reoxygenation [38].…”
Section: Introductionmentioning
confidence: 96%